Reductive dechlorination of carbon tetrachloride using buffered alkaline ascorbic acid. (October 2015) - Lin, Ya-Ting; Liang, Chenju
Graphical abstract: Highlights: Alkaline ascorbic acid (AA) was discovered as a novel ISCR reagent. Alkaline AA using elevated NaOH and phosphate buffer promote the reducing ability. Maintaining a high alkaline condition is crucial for producing e − transfer from AA. Carbon balance confirms threonic and oxalic acids as major AA degradation products. Abstract: Alkaline ascorbic acid (AA) was recently discovered as a novel in-situ chemical reduction (ISCR) reagent for remediating chlorinated solvents in the subsurface. For this ISCR process, the maintenance of an alkaline pH is essential. This study investigated the possibility of the reduction of carbon tetrachloride (CT) using alkaline AA solution buffered by phosphate and by NaOH. The results indicated that CT was reduced by AA, and chloroform (CF) was a major byproduct at a phosphate buffered pH of 12. However, CT was completely reduced by AA in 2 M NaOH without CF formation. In the presence of iron/soil minerals, iron could be reduced by AA and Fe 2+ tends to precipitate on the mineral surface to accelerate CT degradation. A simultaneous transfer of hydrogenolysis and dichloroelimination would occur under phosphate buffered pH 12. This implies that a high alkaline environment is a crucial factor for maintaining the dominant pathway of two electron transfer from dianionic AA to dehydroascorbic acid, and to undergo dichloroelimination of CT. Moreover, threonic acid and oxalic acid were identified to be the major AA decomposition products in alkaline solutions.